Multiple Protocols Combined with Hyperbaric Oxygen Therapy on the Maintenance of Ovarian Function in Patients After Ovarian Cystectomy - Yu, Jie; Qi, Yin-Liang; Lu, Da-Wei; Fang, Qian-Jin; Li, Lan; Sang, Lin (Frontiers in Surgery, 2022)
Objective This study aims to explore the effect of adjuvant hyperbaric oxygen therapy on ovarian function after laparoscopic ovarian cystectomy. Methods A total of 60 patients with ovarian cysts treated at our hospital from January 2018 to August 2020 were enrolled. According to the different treatment modalities, the patients were divided into the control and observation groups. Patients in both groups underwent laparoscopic ovarian cystectomy with oral administration of Chinese patent medicine Kuntai capsules after surgery. Hyperbaric oxygen therapy was added to patients in the observation group in addition to the treatment in the control group. The anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), and antral follicle count (AFC) serum levels were detected in both groups before the operation and at the first and third menstrual cycles postoperatively to evaluate ovarian function. Results At the first and third menstrual cycles after surgery, the AMH, E2, and AFC serum levels in the two groups were significantly lower than before surgery, and the FSH and LH serum levels were higher than before surgery. The differences were statistically significant (P < 0.05). After the operation, AMH, E2, and AFC serum levels in the observation group were significantly higher than in the control group. FSH and LH serum levels were significantly lower than in the control group, and the differences were statistically significant (P < 0.05). Conclusion For patients undergoing laparoscopic ovarian cystectomy, the adjuvant hyperbaric oxygen therapy could significantly improve the postoperative ovarian reserve function with remarkable effects.